Electrochemical Synthesis of Sm-Ni Alloy Magnetic Materials by Co-reduction of Sm(III) and Ni(II) in LiCl-KCl-SmCl3-NiCl2 Melt. Issue 13 (1st January 2016) - Liu, Yu-Hui; Yan, Yong-De; Zhang, Mi-Lin; Zheng, Jia-Ning; Yang-Zhao,; Wang, Pu; Yin, Tai-Qi; Xue, Yun; Jing, Xiao-Yan; Han, Wei
Abstract : This work presented the electrochemical synthesis of Sm-Ni alloy magnetic materials by co-reduction of Sm(III) and Ni(II) ions on a Mo electrode or a nickel coated Mo electrode in molten LiCl-KCl-SmCl3 -NiCl2 at 873 K. The electrochemical behaviors of Sm(III), Ni(II) ions and alloy formation in the melt were investigated by cyclic voltammetry (CV), square wave voltammetry (SWV) and open-circuit chronopotentionmetry (OCP) techniques. The Sm-Ni alloys were obtained on Mo electrode by potentiostatic electrolysis with the varied potential at −0.8 V, −1.5 V, −1.8 V and −2.2 V (vs. Ag + /Ag), respectively. Afterwards, all the Sm-Ni alloys were characterized by X-ray diffraction (XRD), the results indicated that the Smx Niy alloys (SmNi5, SmNi2 and SmNi) were prepared on Mo electrode successfully. The microstructure and micro-zone chemical analysis of Sm-Ni alloys were characterized by scanning electron microscopy (SEM) with energy dispersive spectrometry (EDS). The X-ray photoelectron spectroscopy (XPS) was performed to investigate the surface composition. The results showed that valence states of Sm and Ni on the surface were zero, which were consistent with the peak of the Sm and Ni standard spectra of metals. Vibrating sample magnetometer (VSM) tests illustrated that the magnetization intensity reached the saturated state along magnetic domain direction.